Empty shells. vol. 2, - Spurrier, Simon (The Dreaming, 2020)
"Simon Spurrier and Bilquis Evely continue the stories of the characters from the award-winning The Sandman series by Neil Gaiman as Lord Daniel is introduced to the cold taste of heartbreak. And as expected, it's not pretty. Even the Lord of Dreams is powerless against the storm of lost love. As with his predecessor Morpheus, Lord Daniel will find love in the last place anyone could have hoped for...the realm of the mortals. And as with all romantic entanglements between mortals and the Endless, things are destined to be doomed. Meanwhile, a newly awakened mind in the Dreaming brings with it radical changes that may undo reality itself!"--